2000
DOI: 10.1002/(sici)1097-4628(20000307)75:10<1261::aid-app7>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an adsorbent by graft polymerization of acrylamide onto coconut husk for mercury(II) removal from aqueous solution and chloralkali industry wastewater

Abstract: Graft copolymerization of acrylamide onto coconut husk (CH), initiated by the ferrous ammonium sulfate/H 2 O 2 redox initiator system, was studied. To determine the optimum conditions of grafting, the effect of the concentrations of ferrous ammonium sulfate, the monomer, and H 2 O 2 and the time and temperature on percentage of the graft yield was studied. A new adsorbent media having a carboxylate functional group was synthesized by the surface modification of polymer-grafted coconut husk (PGCHOCOOH). The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
(14 reference statements)
0
16
0
1
Order By: Relevance
“…This side group acts as a handle so that the -COOH group is more to protrude with the aqueous solution. Earlier workers have also reported the same spacer effect of the side group present in the carboxylic acid-functionalized synthetic polymers for their unusual binding capacities towards metal ions [22,23]. As such subsequent adsorption experiments with Cr(III) were performed on SDGPMA-SP-COOH.…”
Section: Effect Of Chemical Modification On Cr(iii) Adsorptionmentioning
confidence: 82%
See 1 more Smart Citation
“…This side group acts as a handle so that the -COOH group is more to protrude with the aqueous solution. Earlier workers have also reported the same spacer effect of the side group present in the carboxylic acid-functionalized synthetic polymers for their unusual binding capacities towards metal ions [22,23]. As such subsequent adsorption experiments with Cr(III) were performed on SDGPMA-SP-COOH.…”
Section: Effect Of Chemical Modification On Cr(iii) Adsorptionmentioning
confidence: 82%
“…The presence of side group [-CONH-(CH 2 ) 2 -NH-CO-(CH 2 ) 2 -] on SDGPMA-SP-COOH can affect the adsorption reaction by its spacer effect [22]. To examine the spacer effect of the side group in SDGPMA-SP-COOH on Cr(III) adsorption, the amount of adsorbent dose required for complete removal of Cr(III) from 50.0 mL of 25.0 mg/L solution for SDGPMA-SP-COOH was compared with that obtained for an adsorbent having -COOH functional group without side group (SDGPMA).…”
Section: Effect Of Chemical Modification On Cr(iii) Adsorptionmentioning
confidence: 99%
“…This result may be explained by considering the chemical structure of the two materials (Table 2). Pozzolana has a higher concentration of sulphur and phosphate which form mercury complexes and are eventually used to increase the mercury adsorption capacity of sorbents [33][34][35][36]. Similarly the content of iron oxides, which present a good mercury adsorption capacity [37], is higher for the pozzolana rather than for the yellow tuff.…”
Section: Resultsmentioning
confidence: 99%
“…Several extensive studies have also been performed using activated carbon prepared from agricultural wastes for the removal of mercury from aqueous solutions such as peanut hull carbon [15], olive stones [16], and Sugi wood [17]. In addition, chemically treated sorbents including coconut husks [18], bagasse pith [19], bark [20], and polyacrylamide-grafted banana stalks [21], have been used in attempts to enhance the mercury sorption performance. Most of this work has shown that agricultural products and waste by- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%